2020
DOI: 10.21203/rs.3.rs-114695/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Exposure to Silver Nanoparticles Leads to Long Term Gut Dysbiosis and Neurobehavioral Alterations

Abstract: Due to their antimicrobial properties, silver nanoparticles (NPs) are used in a wide range of consumer products that includes topical wound dressings, coatings for biomedical devices, and food-packaging to extend the shelf-life. Despite their beneficial antimicrobial effects, developmental exposure to such NPs may lead to gut dysbiosis and long-term health consequences in exposed offspring. Silver NPs can cross the placenta and blood-brain-barrier to translocate in the brain of offspring. The underlying hyp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have reported gut microbial shifts and changes in species abundance after oral exposure to silver and titanium dioxide NPs, both used in a wide range of consumer products such as food packaging and industrial Environmental Science: Nano Paper baked goods, respectively. 43,44 Hence, due to the wide and increasing use of NPs (organic and inorganic) in the food industry (food additives, food supplements or food packaging), a growing interest in studying the impacts of foodborne NPs on the intestinal microbiota has emerged. Moreover, chronic GI exposure to NPs, including direct effects on microbiota and indirect effects due to NP-mediated immune system dysfunctions, require further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported gut microbial shifts and changes in species abundance after oral exposure to silver and titanium dioxide NPs, both used in a wide range of consumer products such as food packaging and industrial Environmental Science: Nano Paper baked goods, respectively. 43,44 Hence, due to the wide and increasing use of NPs (organic and inorganic) in the food industry (food additives, food supplements or food packaging), a growing interest in studying the impacts of foodborne NPs on the intestinal microbiota has emerged. Moreover, chronic GI exposure to NPs, including direct effects on microbiota and indirect effects due to NP-mediated immune system dysfunctions, require further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs are widely used for antimicrobial properties in medicine, but this kind of NP can cause alteration in neurobehavioral and organ development in offspring after long-term exposure. AgNPs passing the blood-brain barrier (BBB) and disrupting development in the fetal brain can induce oxidative stress causing sensitivity against infection [57].…”
Section: Nanoparticle Deliverymentioning
confidence: 99%